ISOLASI DAN IDENTIFIKASI MOLEKULER KHAMIR DARI MOLASE SERTA KEMAMPUANNYA DALAM PRODUKSI ETANOL - Fauziah Citra Rahmawati; Endang Kusdiyantini; Anto Budiharjo (Jurnal Akademika Biologi, 2017)
The need of petroleum is increasing while the availability is limited. Petroleum is an alternative energy source which is produced by fermentation using a sugar-containing substrate with the help of yeast. This research aims to isolate the yeast that can ferment molasses into ethanol and identify morphologically, biochemically, and molecular so the species can be known. The isolation is done into the PDA media by streak method. Morphological identification involves macroscopic and microscopic observation. Biochemical identification involves growth tests on 50% glucose concentration and sugar fermentation. Molecular identification is done by looking at its genome based on Internal Transcribed Spacer (ITS) DNA base order. From Molasses isolation was obtained four isolates of yeast, that are isolates 1C1, 1C2, 2C1, and 3C2. Isolates 2C1 which is used for ethanol fermentation produces 0,9876 g/cm3 or 9,5% of ethanol. 2C1 Isolates was amplified using PCR and Phylogenetic Analysis using Neighbor Joining method. Sequencing results show that Isolates 2C1 has 616 bp Query Length. Based on Homology equation through BLAST method and phylogenetic tree analysis, isolates 2C1 is a Debaryomyces Hansenii.Keywords: Identification, Yeast, Molasses, Molecular, Ethanol